The journalistic preference for extreme exemplars: educational socialization, psychological biases, or editorial policy? - Aarøe, Lene; Andersen, Kim; Skovsgaard, Morten; Svith, Flemming; Schmøkel, Rasmus (Journal of Communication, 2024)
Exemplars are central in news reporting. However, extreme negative exemplars can bias citizens' factual perceptions and attributions of political responsibility. Nonetheless, our knowledge of the factors shaping journalistic preferences for including exemplars in news stories is limited. We investigate the extent to which educational socialization, psychological biases, and editorial policy shape journalistic preferences for extreme negative exemplars. We field large-scale survey experiments to a population sample of journalism students, a nationally representative sample of citizens, and a representative sample of "young people" and obtain evaluations of news value, newsworthiness, and behavioral measures of the actual write-up of news articles. We find significant support for the role of editorial policy and limited support for the role of educational socialization and psychological biases. In a time where economic pressures and the proliferation of digital media potentially lead editors to prioritize clickbait, these findings suggest that structural biases in news coverage may be aggravated.